RESEARCH ON SYNERGY CAUSED BY NETWORK EXTERNALITY: THE CASE OF LITHUANIAN FIXED TELEPHONE COMMUNICATIONS MARKET - Ličkus, Petras (Ekonomika, 2011)
The paper presents a theoretical model of synergetic effect and explores the Lithuanian fixed telephone communications market before and after liberalization in accordance with network externality and user utility change when new users login. Based on the developed theoretical model, an empirical research was done. The aim of the research was to investigate the synergetic effect and to show the importance of network externality in the Lithuanian fixed telephone communications market. According to our theoretical model, there may be a situation when, after liberalization and due to increased competition, the profit of the market monopolist (ex) grows. This means that the competition caused by the decrease in revenue is offset by gains in the supply. In this case, the synergetic effect caused by the network externality takes place.